Insights of Phage-Host Interaction in Hypersaline Ecosystem through Metagenomics Analyses - Motlagh, Amir Mohaghegh; Bhattacharjee, Ananda S.; Coutinho, Felipe H.; Dutilh, Bas E.; Casjens, Sherwood R.; Goel, Ramesh K. (Frontiers in Microbiology, 2017)
Bacteriophages, as the most abundant biological entities on Earth, place significant predation pressure on their hosts. This pressure plays a critical role in the evolution, diversity and abundance of bacteria. Additionally, phages modulate the genetic diversity of prokaryotic communities through the transfer of auxiliary metabolic genes. Numerous studies have been conducted in diverse ecosystems to better understand phage-host interactions and their effects on prokaryote metabolism and community composition. However, hypersaline environments remain among the least studied ecosystems and the interaction between the phages and prokaryotes in these habitats is not well understood. This study offers an insight to bridge this gap in knowledge by analyzing bacteriophage-host interactions in the Great Salt Lake, the largest prehistoric hypersaline lake in the Western Hemisphere. Our metagenomics analyses allowed us to comprehensively identify the bacterial and phage communities with Proteobacteria, Firmicutes and Bacteroidetes as the most dominant bacterial species. Additionally, Siphoviridae, Myoviridae, and Podoviridae were found to be the most dominant viral families in the metagenomic sequences. We also characterized interactions between the phage and prokaryotic communities of the Great Salt Lake and determined how these interactions possibly influence the community diversity, structure, and biogeochemical cycles. Furthermore, the presence of prophages and their interaction with the prokaryotic hosts were studied. It showed the susceptibility of the prokaryotic community present in the Great Salt Lake environment could undergo possible prophage induction. This process can occur under different environmental stress factors. We found that nitrate assimilation and carbon cycle were the most susceptible nutrient cycling pathways to prophage induction in the presence of environmental stresses. This study offers an enhanced glimpse of phage and prokaryote abundance and diversity as well as their interactions in a hypersaline complex ecosystem.